Pengelolaan Zakat Untuk Membangun Kesejahteraan Umat Dalam Tinjauan Hukum Ekonomi Syariah - Muhammad Aziz (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2020)
Zakat is an important instrument in building the country's economy. The history of Islam has proven the effectiveness of zakat in eradicating poverty. Looking at the estimated potential of zakat in Indonesia and the existing reality in society, it can be seen that there is a gap between the rich and the poor. The potential for zakat funds in Indonesia is estimated to reach Rp. 200 trillion, while the poverty rate in Indonesia is still high. The meaning of the managed zakat fund is still far from the predicted potential. BAZNAS as the state zakat management institution sees that there are several factors that make this management not optimal. One of them is the lack of trust of the muzakki that arises because the reports on the management of zakat funds by amil zakat institutions are not yet transparent. Apart from trying to increase public trust, BAZNAS implements programs in the fields of health, education and community welfare. As a result of this effort, the poverty rate in Indonesia has gradually decreased, and in the future it is hoped that it can eradicate poverty in Indonesia. Keywords: zakat, management, the role of zakat, zakat program